Penerapan Model Pembelajaran PJOK Inovatif Untuk Meningkatkan Hasil Belajar Materi Kebugaran Jasmani 2 Siswa Kelas V SD Negeri Gunung Gatep - S, Muhammad Guntur (Lembaga Yasin AlSys, 2022)
This classroom action research aims to improve the learning outcomes of physical fitness material 2 for 5th grade students of SD Negeri Gunung Gatep for the academic year 2021/2022 through the application of the innovative PJOK learning model. The sample in this study were 20 students of class V, consisting of 11 male students and 9 female students. Data collection uses the test method with a set of learning outcomes test instruments. The data analysis technique used descriptive quantitative data analysis. The results of data analysis show that the application of innovative learning models can improve student PJOK learning outcomes. This is indicated by the increase in classical kutantan and the average PJOK learning outcomes of students from pre-cycle to cycle II. Students classical mastery increased by 25% from pre-cycle to cycle I, from 40% to 65%. Then it increased by 50% from pre-cycle to cycle II, ie from 40% to 90%. And increased by 25% from cycle I to cycle II, ie from 65% to 90%. Meanwhile, the average student learning outcomes increased by 10 points from pre-cycle to cycle I, ie from 65 to 75. Then increased by 18 points from pre-cycle to cycle II, ie from 65 to 83. And increased by 8 points from cycle I to cycle II, which is from 75 to 83.